Nilai Kebangsaan pada Karya-Karya Leila S. Chudori - Tristanti Apriyani; Baiq Annisa Yulfana Nalurita (Universitas Mulawarman, 2023)
In literary studies, novels carry various ideological values, such as national ideology. Empirical evidence shows that national ideologies can influence and shape regimes nationally and internationally. One of the manifestations of national ideology can be actualized in literary works such as novels and short stories. This research aims to examine the value of nationality in the works of Leila S. Chudori by using the hermeneutic method formulated by Paul Ricoeur. This research is descriptive qualitative research, and the data used are Leila S. Chudori's works, namely 2 novels and 2 short story collections. Meanwhile, data analysis techniques are carried out in three basic stages of hermeneutics formulated by Ricoeur (1975): understanding, discussion, and interpretation. The results show that Leila S. Chudori's works have succeeded in entering the deepest aspects of national values, including psychological, sociological, and historical aspects. The narration in the plot, characters, and themes in Leila S. Chudori's works are able to articulate national values through the characters presented by the author. The narration is related to the memory of Indonesia, love for Indonesia, pride in Indonesia, and Indonesian identity.